440 DUSP5 IS DECREASED BY INTRAUTERINE GROWTH RESTRICTION IN THE THYMUS AND SPLEEN OF NEWBORN RATS. Issue 1 (1st January 2007) - Contreras, Y.; Jeffs, S.; Yu, X.; Hale, M. A.; McKnight, R.; Jenkins, S.; Lane, R.
Abstract : Background: IUGR infants have qualitative and quantitative abnormalities in lymphocyte function that persist into childhood, resulting in increased susceptibility to infections. Little is known about the underlying mechanisms; however, it is thought that epigenetic regulation of gene expression plays a major role in the long-term pathology associated with IUGR. We have previously shown that CD4 + /CD8 + immature T cells in the thymus are disproportionately affected in IUGR. Recently, the dual-specificity phosphatase DUSP5 has been shown to be necessary for immature CD4 + /CD8 + T-cell development in the thymus (Mol Immunol 2006 Feb). Interestingly, DUSP5 also manifests epigenetic alterations in the liver and brain of IUGR rats, with males more affected. Objective: We therefore hypothesized that IUGR decreases DUSP5 mRNA levels in the thymus and spleen and decreases the number of CD4 + /CD8 + cells in the thymus of newborn IUGR rats in a sex-specific manner. Design/Methods: To prove this hypothesis, we used bilateral uterine artery ligation and sham surgery to produce IUGR and control rats ( n = 6 in each group). Thymus and spleen were harvested at birth. Organ weight and total cell number were corrected for body weight differences. mRNA levels were measured in a sex-specific manner with real-time rtPCR in both the thymus and spleen at birth. Flow cytometry was used to analyze the number of CD4 + /CD8 + immature T cells in the thymus at birth. Results: DUSP5 mRNA levels were decreased in the spleen of both male and female rats at birth (78% and 66%, p < .05, n = 6). Thymus levels of DUSP5 mRNA were not altered in males but were decreased in females at birth (84%, p < .05, n = 6). IUGR also decreased double positive (CD4 +, CD8 + ) naive, undifferentiated T cells in the thymus versus controls (72% vs 66%, p < .05) in both males and females. conclusions: We conclude IUGR decreases DUSP5 levels in the thymus and spleen in female rats at day 0. Male rats have decreased DUSP5 levels in the spleen but not the thymus at birth. This is intriguing because decreased DUSP5 levels are associated with impaired development of immature lymphocytes, which is also a hallmark of IUGR. We speculate that decreased perinatal DUSP5 levels lead to decreased development of immature lymphocytes in the thymus, which represents a pathway through which IUGR causes abnormalities in lymphocyte number. Supported by the Children's Health Research Center.